Numerical and Experimental Investigations on Hydrodynamic Performance of a Newly Designed Deep Bottom Trawl - Guan, Qinglong; Zhu, Wenbin; Zhou, Aizhong; Wang, Yongjin; Tang, Weiyao; Wan, Rong (Frontiers in Marine Science, 2022)
In this paper, a new type of bottom trawl was designed for target fishing vessels to use in deep-water fishing grounds. The trawl’s hydrodynamic performance was investigated using numerical simulation and physical modeling methods, and a numerical model based on the finite element method was proposed for estimating hydrodynamic forces and predicting performances. A series of physical model tests based on Tauti’s law were carried out in a towing tank to explore the hydrodynamic performance of the trawl and to assess the applicability of the numerical simulation method. The results showed that the working towing speed of the trawl was 3.5 kn. The drag force and the height of net opening were 50 kN and 5.62 m, respectively, and the swept area was 128 m2 at that speed. The simulated result was close to the experimental result, with a maximum relative error less than 20%, and an average relative error of 10%. The net shape and tension distribution of the trawl were analyzed using the numerical simulation method, and the hanging ratio in T-direction of the mesh of the codend was 0.25 at the working towing speed. The newly designed deep bottom trawl had a superior hydrodynamic performance for high catch efficiency and selectivity and may be applied to commercial fishing operations.